Portfolio Selection with an Imperfectly Competitive Asset Market - James, John A. (Journal of Financial and Quantitative Analysis, 1976)
Traditional models of portfolio selection assume that all assets are traded in competitive markets, so that rates of return to any individual investor are fixed. This paper represents an extension of portfolio theory to the case in which asset markets are not perfectly competitive and rates of return cannot be taken as given. Klein [10] has noted that, when asset markets are imperfect, the separation theorem no longer holds but does not solve explicitly for the relationship between risk and return. Here for simplicity we shall consider the case of the investor who has a monopoly in an asset he creates, so that its risk and return characteristics are determined by the decisions of the portfolio selector and hence are endogenous. It will be shown that even if the market for an asset in the portfolio is imperfectly competitive, as long as the demand curve for the asset is well behaved, the locus of efficient portfolios facing the investor, which is composed of combinations of the riskless asset and the optimal combination of risky assets, will be a concave function, as opposed to a linear function in the competitive case. In other words, the introduction of capital market imperfections does not affect the positive slope of the efficient set of portfolios. Moreover, the expected return on the imperfectly competitive asset will be shown to be easily decomposable into the standard risk premium and a monopoly premium.